Escalation of Visual Accentuation of the Connecting Corridor of the Grand Mosque Bakrie Area for Strengthening the Identity of Kisaran City - Shirin Alya Yasmin; Rinaldi Mirsa; Muhammad Abdul Rahman (Electronic Journal of Education, Social Economics and Technology, 2025)
The Bakrie Mosque is a religious tourism area with strategic potential in shaping the identity of the city. This study discusses the concepts of accentuation and escalation in the development of the mosque area as an effort to strengthen its appeal, social function, and city image. Accentuation is understood as the affirmation of the visual, architectural, and narrative character of the area, while escalation refers to the increase in capacity, facilities, and diversification of tourism activities. The study aims to identify visual characteristics and formulate design guidelines that align the public corridor with the mosque's grandeur. Using a qualitative descriptive approach with a case study strategy, data were collected through structured observation and visual recording of street elements within a 500-meter radius. The results indicate that applying these concepts contributes significantly to creating a sustainable tourism ecosystem and positioning the Bakrie Mosque as a representative city icon. The analysis reveals a visual disparity between the landmark and micro-street elements, necessitating a "Visual Harmonization" strategy. This article provides a conceptual perspective that can be utilized in development strategies for other religious tourism areas.